Analysis Of The Relationship Of Blood Sugar Control In Patients With Diabetes Mellitus With Compliance To Take Medicine In Balimbingan Hospital In 2019 - Erni Karmila; Sri Lestari Ramadhani Nasution; Ermi Girsang; Ali Napiah Nasution (CV. Inara, 2022)
Diabetes mellitus is a major public health problem because of its short-term and long-term complications. Diabetes Mellitus (DM) is a disease that involves pancreatic endocrine hormones, including insulin and glucagon. The main manifestations include disturbances of lipid, carbohydrate, and protein metabolism, which in turn stimulates hyperglycemia. This hyperglycemic condition will develop into diabetes mellitus with various forms of complications. Adherence is very important, especially in long-term treatment. In general, the level of compliance in each patient is described by the percentage of the number of drugs taken and the time of taking the drug within a certain period of time. This study aims to determine the relationship between controlled blood sugar in patients with diabetes mellitus with medication adherence at Balimbingan Hospital. The design of this study was cross sectional, with a quantitative approach with a sample of 56 patients. The data collection method in this study used a questionnaire and data on visits to patients with diabetes mellitus at Balimbingan Hospital.